Assessing the importance of Isle of Man waters for the basking shark Cetorhinus maximus - Dolton, H; Gell, F; Hall, J; Hall, G; Hawkes, L; Witt, MJ (Endangered Species Research, 2019)
This is the final version. Available on open access from Inter Research via the DOI in this record Satellite tracking of endangered or threatened animals can facilitate informed conservation by revealing priority areas for their protection. Basking sharks (Cetorhinus maximus, n=11) were tagged during the summers of 2013, 2015, 2016 and 2017 in the Isle of Man (IoM; median tracking duration 378 days (range: 89-804 days); median minimum straight-line distance travelled 541 km (range: 170-10,406 km). Tracking revealed three movement patterns: (i) coastal movements within IoM and Irish waters, (ii) summer northward movements to Scotland and Norway and (iii) international movements to Morocco and Norway. One tagged shark was bycaught and released alive in the Celtic Sea. Basking sharks displayed inter-annual site fidelity to the Irish Sea (n=3), a Marine Nature Reserve (MNR) in IoM waters (n=1), and Moroccan waters (n=1). Core distribution areas (50% kernel density estimation) of five satellite tracked sharks in IoM waters were compared with 3,902 public sightings between 2005 and 2017, highlighting West and South coast hotspots. Location data gathered from satellite tagging broadly corresponds to the current boundaries of MNRs in Manx waters. However, minor modifications of some MNR boundaries would incorporate ~20% more satellite tracking location data from this study, and protective measures for basking sharks in IoM waters could further aid conservation of the species at a local, regional and international scale. We also show the first documented movement of a basking shark from the British Isles to Norway, and the longest ever track for a tagged basking shark (two years and two months, 804 days).